Topical issues of Internet impact on teen suicidal behavior - Asieieva, Yuliia (Journal of Education, Health and Sport, 2017)
For the time being, the social network Internet acts as a direct platform for the realization of the need for self-presentation, self-identification and self-realization. There is no limit to the content of the Internet, in addition to scientific, political, economic information, there are also negative information platforms with aggressive, sexual and other negative information that have an effect on the network users. This paper focuses on analyzing the spread of suicidal information on the Internet about how to formulate guidelines for suicidal behavior. The author analyzes the contemporary specific literature on the phenomenon of suicide, analyzes the communication space available to the population of our country - social and search networks. This problem is considered in the context of the development and spread of communication on the Internet deviant subcultures and their negative impact on the adoption of norms, values and behaviors by young people. This study is a pilot study conducted to identify current trends in the impact of the Internet on adolescent behavior, including suicidal ones, with a view to further developing both algorithms for an individual complex program of psychosocial rehabilitation and group psycho-corrective programs that take into gender.